Smart factory implementation and process innovation : a preliminary maturity model for leveraging digitalization in manufacturing moving to smart factories presents specific challenges that can be addressed through a structured approach focused on people, processes, and technologies - Sjödin, David R.; Parida, Vinit; Leksell, Markus; Petrovic, Aleksandar (Taylor & Francis, 2018)
The development of novel digital technologies connected to the Internet of Things, along with advancements in artificial intelligence and automation, is enabling a new wave of manufacturing innovation. “Smart factories” will leverage industrial equipment that communicates with users and with other machines, automated processes, and mechanisms to facilitate real-time communication between the factory and the market to support dynamic adaptation and maximize efficiency. Smart factories can yield a range of benefits, such as increased process efficiency, product quality, sustainability, and safety and decreased costs. However, companies face immense challenges in implementing smart factories, given the large-scale, systemic transformation the move requires. We use data gathered from in-depth studies of five factories in two leading automotive manufacturers to analyze these challenges and identify the key steps needed to implement the smart factory concept. Based on our analysis, we offer a preliminary maturity model for smart factory implementation built around three overarching principles: cultivating digital people, introducing agile processes, and configuring modular technologies.
Keywords: smart factory; process innovation; industry 4.0; digitalization; maturity model; fi=Johtaminen ja organisaatiot|en=Management and Organization|